Pengaruh Deviasi Mutu Tulangan Beton hasil pengujian Terhadap Desain Balok Beton Bertulang Bertulangan Lemah - Ruminsar ok Simbolon (Universitas Mulawarman, 2026)
Reinforced concrete is a composite material that utilizes concrete and reinforcing steel to withstand tensile and flexural forces. However, the reinforcement ratio used in reinforced concrete beams significantly affects the strength, deformation, and collapse patterns of the structure. This study aims to analyze the effect of deviations in concrete reinforcement quality testing results on the planned collapse behavior of reinforced concrete beams in under-reinforced conditions. This research method uses a laboratory experimental approach with tensile testing on reinforcing steel by considering the deviation limit values according to SNI. Data analysis was carried out by comparing the results of the flexural capacity analysis of weakly reinforced concrete beams with a yield stress value of fy = 420 MPa with the realization of the flexural capacity of weakly reinforced concrete beams with a yield stress value based on laboratory testing results. The results show that reinforced concrete beams planned for under-reinforced failure tend not to be met and become over-reinforced beams, so that the expected behavior of reinforced concrete beams changes to brittle failure. This finding confirms that the selection of the flexural reinforcement ratio in the planning stage must consider the possibility of higher reinforcement quality deviations from the planning target, so that the planning target of weakly reinforced concrete beams can still be met